Terrorism - Friedman, Lauri S. (Detroit, Michigan Greenhaven Press, 2011)
Explores the issue of terrorism by placing opinions from a wide range of sources in a pro/con format. Features articles that express various perspectives on this topic.
How serious is the terrorist threat? -- What should the United States do to prevent terrorism? -- How should suspected terrorists be treated?
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Terrorism; Terrorism -- Prevention; Electronic books